Foraging behaviour of the Scale-throated Hermit Phaethornis eurynome Lesson, 1832 (Aves, Trochilidae) in Vriesea incurvata Gaudich (Bromeliaceae) - BG. Silva; AJ. Piratelli (Brazilian Journal of Biology)
In this study we tested for density-dependent relationships between visitation rates of the Scale-throated Hermit (Phaethornis eurynome) and the plant density and flower number of the bromeliad Vriesea incurvata, by comparing plots with varying densities of this bromeliad. Eight 100 m2 plots were established at least 200 m from each other; four plots contained 10-15 individuals of V. incurvata each, whereas the other four contained 4-5 individuals each. The visitors, number of visits, behaviour (nectar thief or potential pollinator) and the height of foraging were recorded during focal observations on the plants. The number of visits of P. eurynome varied according to the local density of V. incurvata, showing that the heterogeneous distribution of this bromeliad species may promote adjustments in the pollinator populations, through resource variation at a local scale.